Crosstalk between human immunodeficiency virus infection and salivary bacterial function in men who have sex with men - Guo, Ying; Wang, Wenjing; Yu, Yixi; Sun, Xintong; Zhang, Baojin; Wang, Yan; Cao, Jie; Wen, Shuo; Wang, Xin; Li, Yuchen; Cai, Siyu; Wu, Ruojun; et al. (Frontiers in Cellular and Infection Microbiology, 2024)
Background: Engaging in anal sexual intercourse markedly increases the risk of developing HIV among men who have sex with men (MSM); oral sexual activities tend to uniquely introduce gut-derived microbes to salivary microbiota, which, combined with an individual’s positive HIV status, may greatly perturb oral microecology. However, till date, only a few published studies have addressed this aspect. Methods: Based on 16S rRNA sequencing data of bacterial taxa, MicroPITA picks representative samples for metagenomic analysis, effectively revealing how the development and progression of the HIV disease influences oral microbiota in MSM. Therefore, we collected samples from 11 HIV-negative and 44 HIV-positive MSM subjects (stage 0 was defined by HIV RNA positivity, but negative or indeterminate antibody status; stages 1, 2, and 3 were defined by CD4+ T lymphocyte counts ≥ 500, 200–499, and ≤ 200 or opportunistic infection) and selected 25 representative saliva samples (5 cases/stage) using MicroPITA. Metagenomic sequencing analysis were performed to explore whether positive HIV status changes salivary bacterial KEGG function and metabolic pathway in MSM. Results: The core functions of oral microbiota were maintained across each of the five groups, including metabolism, genetic and environmental information processing. All HIV-positive groups displayed KEGG functions of abnormal proliferation, most prominently at stage 0, and others related to metabolism. Clustering relationship analysis tentatively identified functional relationships between groups, with bacterial function being more similar between stage 0-control groups and stage 1-2 groups, whereas the stage 3 group exhibited large functional changes. Although we identified most metabolic pathways as being common to all five groups, several unique pathways formed clusters for certain groups; the stage 0 group had several, while the stage 2 and 3 groups had few, such clusters. The abundance of K03046 was positively correlated with CD4 counts. Conclusions: As HIV progresses, salivary bacterial function and metabolic pathways in MSM progressively changes, which may be related to HIV promoting abnormal energy metabolism and exacerbate pathogen virulence. Further, infection and drug resistance of acute stage and immune cell destruction of AIDS stage were abnormally increased, predicting an increased risk for MSM individuals to develop systemic and oral diseases.